Teachers' Strategies in Teaching Speaking Skills at SMAN 1 Palopo - Anggraeni, Widya; Wahibah, Wahibah; Faqihuddin Assafari, Amir (FOSTER: Journal of English Language Teaching, 2020)
The study aimed to know the strategies used by teachers at S.M.A. Negeri 1 Palopo to teach speaking skills. This thesis employed Qualitative Method. The writer applied the purposive sampling technique to obtain the samples of the study. In getting data, the writer examined two English teachers in S.M.A. Negeri 1 Palopo. The writer also used observation-checklist, semi-structured interviews, and reports to get the data. The result of this study showed that teacher 1 used discussion, role-play, brainstorming, writing, conversation, blogging, picture description, and learning assignment. While teacher 2 used conversation, modeling, role-play, brainstorming, writing, questioning, reading, explaining, and playing ice hockey. Both teachers use various strategies in teaching speaking.